Experimental and theoretical studies for I⋯F, I⋯I and I⋯N intermolecular interactions Analysis in 5, 7-diiodoquinoline derivatives and their In-vitro DPP-4 inhibitory activity - Jaiswal A.; Mishra M.; Mitra M.D.; Nidhar M.; Kumar R. (My University, 2025)
5, 7-diiodoquinoline derivatives have been synthesized and characterized to study quantitative intermolecular noncovalent interactions through theoretical and experimental investigations, particularly for interactions involving electronegative atoms like I⋯F, I⋯I, and I⋯N. X-ray crystallography and Hirshfeld surface analysis have been used to perform the quantitative assessments of non-covalent interactions. Using Crystal Explorer 17, the calculations for intermolecular interactions were completed. Further, antidiabetic in-silico and in-vitro DPP-4 inhibitory activity have been done. The silicon studies have been carried out by Schrodinger on 2OLE pdb id. The in-vitro inhibitory DPP- 4 activity was determined by observing the rate of hydrolysis of a substrate Gly-pro-p-nitroanilide taking sitagliptin as a standard drug. The molecular docking and in-vitro studies revealed that all molecules had shown significant DPP-4 inhibitory activity compared to standard drugs sitagliptin. © 2024 Elsevier B.V.